Perovskite Fabrication: Ambient Manipulation of Perovskites by Alternating Electric Field toward Tunable Photovoltaic Performance (Adv. Funct. Mater. 42/2020). (16th October 2020) - Cheng, Zhendong; Ding, Dong; Song, Jingnan; Liu, Feng; Wang, Tun; Hu, Cheng; Ba, Lixiang; Wang, Jiayuan; Liu, Hong; Shen, Wenzhong
Abstract : In article number 2004652, Hong Liu, Wenzhong Shen, and co‐workers apply an alternating electric field as a novel modulation method for perovskite fabrication. The electric field can induce collective ionic motion inside the material and cause significant structural changes such as the size of grains and microstructure of crystal domains. Consequently, the as‐fabricated perovskite shows controllable opto‐electronic properties and impressive environmental stability.